2020
DOI: 10.1038/s41598-020-75595-4
|View full text |Cite
|
Sign up to set email alerts
|

Selenocysteine insertion sequence binding protein 2 (Sbp2) in the sex-specific regulation of selenoprotein gene expression in mouse pancreatic islets

Abstract: Selenoproteins are a group of selenocysteine-containing proteins with major roles in cellular antioxidant defense and thyroid hormone metabolism. Selenoprotein expression is determined by hierarchical mechanisms that result in tissue-specific levels. Current data inadequately explain the abundance of various selenoproteins under normal and pathological conditions, including in pancreatic β-cells. Selenocysteine insertion sequence binding protein 2 (SBP2) is a critical protein in selenoprotein translation that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In vivo, Gpx3 is the only extracellular subtype of the Gpx family, and it is most highly expressed by kidney [47]; however, it is also highly expressed in the pancreas, lung, heart, liver, and skeletal muscle [47]. In a gene expression analysis of mouse islets, Gpx3 was the most highly expressed selenoprotein transcript in both males and females [48]. Several clinical trials had reported single-nucleotide polymorphisms (SNP) in the Gpx3 gene promoter region are associated with cardiovascular disease [49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, Gpx3 is the only extracellular subtype of the Gpx family, and it is most highly expressed by kidney [47]; however, it is also highly expressed in the pancreas, lung, heart, liver, and skeletal muscle [47]. In a gene expression analysis of mouse islets, Gpx3 was the most highly expressed selenoprotein transcript in both males and females [48]. Several clinical trials had reported single-nucleotide polymorphisms (SNP) in the Gpx3 gene promoter region are associated with cardiovascular disease [49][50][51].…”
Section: Discussionmentioning
confidence: 99%